Postpartum atypical haemolytic uraemic syndrome in a pre-eclamptic patient - Tingi, Efterpi; Sabir, Nada; Verghese, Lynda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Postpartum atypical haemolytic uraemic syndrome (aHUS) is a rare manifestation, defined as non-immune haemolytic anaemia, thrombocytopenia, and renal thrombotic microangiopathy (TMA) typically following a normal vaginal delivery. Most cases of aHUS are caused by uncontrolled chronic activation of alternative complement pathway, resulting in microvascular thrombosis, organ ischaemia and damage. aHUS has a poor prognosis, hence up to 65 percent of patients require haemodialysis or have kidney damage or die. We report a case of postpartum atypical haemolytic uraemic syndrome in a 30 year old multiparous woman, who presented with orthopnoea, chest and abdominal pain, seven days following emergency caesarean section due to severe preeclampsia. Clinical examination and several investigations revealed anaemia, thrombocytopenia and renal failure, findings suggestive of thrombotic microangiopathy, therefore she was admitted in ITU where total plasma exchanged was initiated. The patient improved 10 days post ITU admission and discharged home. This case highlights that the TMAs may be indistinguishable clinically from each other, making a formal diagnosis difficult. Atypical HUS should be suspected during the postpartum period in any woman who presents with haeomolytic anaemia, thrombocytopenia and severe renal impairment. Aggressive treatment with plasma exchange may limit vascular injury and improve prognosis.